Impact of Nursing Clinical Learning During the COVID-19 Pandemic - Suryadi Suryadi; Andi Masyitha Irwan; Takdir Tahir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the impact of clinical nursing learning during the COVID-19 pandemic. The research method used in this research is literature review research using source search articles in the PubMed database with inclusion criteria from 2020 to 2022 and providing full text. The keywords used were